2001
DOI: 10.1002/etc.5620200915
|View full text |Cite
|
Sign up to set email alerts
|

The sheepshead minnow as an in vivo model for endocrine disruption in marine teleosts: A partial life‐cycle test with 17α‐ethynylestradiol

Abstract: The sheepshead minnow (Cyprinodon variegatus Lacépède), an estuarine fish species, was exposed to 17alpha-ethynylestradiol (EE2) at nominal test concentrations of 0.2, 2, 20, 200, 400, 800, 1,600, and 3,200 ng/L. Fish were exposed for up to 59 d, from subadult stages to sexual maturity, under flow-through conditions. The exposure period was followed by an evaluation of reproductive success and survival of progeny. The reproductive success of exposed sheepshead minnows, as determined from data on egg production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 38 publications
(66 reference statements)
11
69
1
Order By: Relevance
“…After 10 days exposure there was complete reproductive failure (no egg production) in the 50 ng/L EE 2 exposure group. These data support previous findings for high dosage, short-term effects of EE 2 (Lange et al 2001; Scholz and Gutzeit 2000; Seki et al 2002; Van den Belt et al 2002; Zillioux et al 2001), and this treatment was subsequently terminated. There were no effects, however, of any other estrogen treatment on numbers and viability of eggs from the F 0 generation at 14 hpf (Figure 2), embryo mortality in the F 1 generation ( F = 0.36, p = 0.78, n = 12), or impacts on larval integrity at 100 hpf; the proportion of developmental abnormality, hatch rate, and level of spine curvature were all not significantly different from controls; p > 0.05 for all cases.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…After 10 days exposure there was complete reproductive failure (no egg production) in the 50 ng/L EE 2 exposure group. These data support previous findings for high dosage, short-term effects of EE 2 (Lange et al 2001; Scholz and Gutzeit 2000; Seki et al 2002; Van den Belt et al 2002; Zillioux et al 2001), and this treatment was subsequently terminated. There were no effects, however, of any other estrogen treatment on numbers and viability of eggs from the F 0 generation at 14 hpf (Figure 2), embryo mortality in the F 1 generation ( F = 0.36, p = 0.78, n = 12), or impacts on larval integrity at 100 hpf; the proportion of developmental abnormality, hatch rate, and level of spine curvature were all not significantly different from controls; p > 0.05 for all cases.…”
Section: Resultssupporting
confidence: 90%
“…A mean of 91.5% of the eggs were fertilized and survived to 100 hpf (posthatch) in all treatments before exposure and in control treatments throughout the experiment. This level of fertilization and survival is high when compared to similar studies on zebrafish (Hill and Janz 2003), sheepshead minnows ( Cyprinodon variegatus ; Zillioux et al 2001), and medaka ( Oryzias latipes ; Balch et al 2004), where lower survival (70, 65, and 62%, respectively) in controls probably relates to suboptimal breeding conditions or stresses associated with embryo culture.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Zillioux et al [42] also reported oocyte atresia in sheepshead minnows exposed to EE2 except at the lowest concentration of 0.2 ng/L. In the present study, a substantial increase in oocyte atresia was seen in the two high-dose groups, with as many as 30 to 40 atretic oocytes seen in a single section of ovary.…”
Section: Discussionsupporting
confidence: 63%
“…Zillioux et al [42] also reported oocyte atresia in sheepshead minnows exposed to EE2 except at the lowest concentration of 0.2 ng/L. Zillioux et al [42] reported that sheepshead minnows exposed to EE2 displayed testis-ova at concentrations ranging from 20 to 800 ng/L. Fathead minnows exposed to E2 also showed an increase in atretic follicles compared to controls [44].…”
Section: Discussionmentioning
confidence: 97%